Pengaruh Blansir dan Konsentrasi CMC terhadap Karakteristik Sirup Kulit Kopi Robusta (Coffea canephora) - Nisah, Adinda Khairun; Romauli, Nauas Domu Marihot (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2025)
Coffee processing frequently generates large amounts of coffee husk waste due to the absence of subsequent utilization, thereby contributing to environmental pollution. However, the presence of antioxidant compounds in coffee husk waste offers potential for its valorization into functional food products such as syrup beverages. The formulation of syrup requires the addition of stabilizing and thickening agents, such as carboxymethyl cellulose (CMC), to maintain product stability and achieve a desirable viscosity that meets consumer preferences. Blanching is applied to improve the characteristics of the syrup product. This study aimed to investigate the potential of robusta coffee husk as a natural source of antioxidants and to evaluate the effects of varying CMC concentrations on the physicochemical and sensory properties of coffee husk syrup. Three blanching treatments—no blanching, hot water blanching, and steam blanching—were applied to the coffee husks, combined with CMC concentrations of 0.05%, 0.10%, and 0.15%. Among all treatments, the combination of steam blanching and 0.10% CMC produced the most favorable results, with IC₅₀ (175.51 μL/mL), L* (31.82), a* (7.57), b* (9.26), color index (50.58 °Hue), total dissolved solids (72.71 °Brix), viscosity (68.73 cP), and total microbes (3.1×10² CFU/mL). These values meet the quality requirements established by the Indonesian National Standard for syrup products (SNI 3544:2013), which specifies a maximum total plate count of 5.0×10² CFU/mL.